The Effect of Erwinia amylovora Infection in Apple Saplings and Fruit on the Behavior of Delia platura (Diptera: Anthomyiidae). Issue 1 (8th December 2020) - Boucher, Matthew; Collins, Rowan; Hesler, Stephen; Cox, Kerik; Loeb, Greg
Abstract: The Vector Manipulation Hypothesis (VMH) posits that phytopathogens develop strategies to enhance dissemination by mediating behavior change in insect vectors. The VMH is poorly studied in phytopathogenic bacteria, especially in systems with numerous, occasional vectors. Erwinia amylovora is a bacterial pathogen of pome fruit that produces a bacterial ooze and is mechanically vectored by insects after they feed on ooze. The blossom blight phase of the disease exhibits manipulation of honeybees, leading to enhanced transmission, but whether the same occurs during the shoot blight phase of the disease is unknown. The goal of this study was to evaluate the effect of E. amylovora on the behavior of Delia platura, a fly with a worldwide endemic presence that may transmit E. amylovora . We show that D. platura prefer infected, oozing fruit to uninfected fruit in choice tests and that preference subsides when bacterial ooze is removed from the infected fruit. Flies did not exhibit a preference between infected saplings and uninfected saplings. The volatiles of infected fruit did not attract D. platura, indicating that diseased fruit odor is not responsible for the observed preference for infected fruit. Flies did not differentiate between sapling odors until infected trees had died, at which point they preferred uninfected tree odors. This study supports previous hypotheses suggesting that E. amylovora takes advantage of existing plant–insect interactions, though it is not fully understood how significantly behavioral changes affect transmission. Additional pathosystems with occasional, nonspecific vectors should be studied to further understanding of the VMH.